Indonesia Pengaruh Belanja Pemerintah di Bidang Pendidikan, Kesehatan dan Inflasi Terhadap Indeks Pembangunan Manusia dan Kemiskinan di Sulawesi Selatan - rahayu ningsih, iffah (ICOR: Journal of Regional Economics, 2023)
This study aims to analyze how much influence government spending in the education, health and inflation sectors have on poverty and the human development index in South Sulawesi. By using time series data for the period 2001-2020 with the pathanalysis method. The calculation data in this study used the Amos version 21 program. The results of this study indicated that partially the variables of expenditure on government education and health had a positive and significant effect on the human development index in South Sulawesi. Inflation has a negative and significant effect on the Human Development Index in South Sulawesi. Government spending on education has a negative and insignificant effect on poverty in South Sulawesi. Government spending on health has a positive and significant effect on poverty in South Sulawesi. Inflation has a negative and insignificant effect on poverty in South Sulawesi. Poverty has a positive and insignificant effect on the Human Development Index in South Sulawesi. di SulawesiSelatan.